Single-stage production of miscanthus hydrochar at low severity conditions and application as adsorbent of copper and ammonium ions. (October 2021) - Georgiou, Efthalia; Mihajlović, Marija; Petrović, Jelena; Anastopoulos, Ioannis; Dosche, Carsten; Pashalidis, Ioannis; Kalderis, Dimitrios
Highlights: A new valorization pathway for miscanthus residues was developed. Single-stage, low severity hydrothermal carbonization produced efficient adsorbents. q max values of 71 and 301 mg g −1 were achieved, for NH4 + and Cu 2+, respectively. Outer- and inner-sphere complexation with NH4 + and Cu 2+, respectively, was observed. Abstract: In the framework of bio-circular economy, miscanthus biomass was valorized through a single-stage, low severity hydrothermal carbonization process. The produced hydrochars were characterized using elemental and spectroscopic methodologies. It was determined that as the temperature increased so did the C content (47.9 and 68.9% for the samples prepared at 180 and 260 °C, respectively), whereas the O content decreased (from 44.2 to 25.5%, respectively). The adsorption behaviour of the hydrochars was investigated in the adsorption of Cu 2+ and NH4 + and MIS-180 was determined as the optimum sample, achieving q max values of 310 and 71 mg g −1, respectively. Isotherm and kinetic analysis indicated the higher number of O-containing functional groups of MIS-180 as the main reason for its higher adsorption capacities. Furthermore, Cu 2+ adsorption followed the 2nd-order kinetic model, whereas NH4 + adsorption followed the 1st-order kinetic model, due to the different mechanisms involved, inner-sphere and outer-sphere complex formation, respectively.